Aspekt sekurytyzacji i hazardu moralnego w prognozowaniu działalności lokacyjnej firmy ubezpieczeniowej - Lawędziak, Bartosz; Szkutnik, Włodzimierz (Aspects of Securitisation and Moral Hazard in Previsions of Financial Investments in Insurance Companies, 2006)
The article presents the analysis (based on a simple model) of effect of the efficiency of risk division on account of utilisation of instruments related to disaster indicator. A decision to manage the risk (property) of the company is being discussed. It is important that there is a possibility to purchase security of an index type that determines catastrophe scale and is a variable of a purchased instrument by a major insurer. Negative side of this kind of instrument is that so called basic risk can appear and at the same time it's not an ideal insurance for the company. To diminish negative effects insurance contract can be introduced (reinsurance) the cover a gap between actual loss and index insurance. In conclusion we try to define most effective ways of company investments which help to avoid financial risk and at the same time increase company's profits.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 248-259